Música em tempos sombrios: apontamentos sobre a estética musical no III Reich - Tomás, Lia [UNESP] (Escola de Música da UFMG, 2016)
In the Third Reich, music occupied a prominent role among the arts, being heavily used as an ideological tool. The aesthetic guidelines proposed by Goebbels in 1938 were based on an ideology already pointed out by Quantz and Wagner, but whose context, in order to fulfill other purposes, distanced from the original context. Departing from an analysis of these authors' texts, this article seeks to demonstrate the appropriation of the central ideas and their transformations, as well the creation of a different category of music, namely, the musical monuments.

No Terceiro Reich, a música ocupou um papel de destaque entre as artes, pois foi maciçamente utilizada como instrumento ideológico. As diretivas estéticas propostas por Goebbels em 1938 tomavam por base um ideário já apontado em Quantz e Wagner, mas cuja reatualização distanciava-se do contexto original para cumprir outros fins. A partir de análises dos textos dos autores citados, o artigo visa demonstrar a apropriação das ideias centrais e suas transformações, bem como a criação de uma outra categoria de música, a saber, os monumentos musicais.
Music in Dark Times: Notes on the Musical Aesthetics in the III Reich
Keywords: Music in the Third Reich; Wagner and Quantz; Goebbels and musical monuments.; Música no Terceiro Reich; Wagner e Quantz; Goebbels e monumentos musicais.